Sistem Informasi Presensi Karyawan Berbasis Web dan SMS Gateway di SMK Dr. Indra Adnan Indragiri College - Niswah, Muhlishatun; Zulrahmadi (Indra Institute Research & Publication, 2023)
In the employee percentage management information system running at SMK Dr. Indra Adnan Indragiri Collage Tembilahan still uses a simple method or in writing, where employees fill in attendance data when they enter working hours. In every attendance activity, there is often fraud by employees who leave their signatures or fill out attendance lists according to their arrival so that the finance department cannot control the delays of employees who come beyond the time set by SMK Dr. Indra Adnan Indragiri Collage Tembilahan, or go home earlier than the specified time. In designing an employee attendance management information system, the author uses a modeling tool, namely UML where the diagrams used are Usecase diagrams, Activity diagrams and class diagrams. The results of this study are in the form of designing a Web-Based Employee Attendance Management Information System prototype and SMS Gateway that can assist in overcoming the problems that occur in Dr. Vocational High School. Indra Adnan Indragiri Collage Tembilahan.